2015
DOI: 10.1097/ajp.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Pain and Nausea in Postoperative Patients for 1 Week After Ambulatory Surgery

Abstract: Younger patients and those receiving orthopedic procedures may be at greatest risk for postoperative pain. Patients with high pain reported a significantly greater degree of nausea on DOS through the first 5 days postdischarge. As the majority of surgeries are now conducted in the ambulatory setting, it is imperative that we determine pain management regimens and patient education practices that will allow for a more comfortable recovery for our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 42 publications
2
32
1
Order By: Relevance
“…Studies identify both orthopedic procedures and younger age as independent risk factors for higher reported pain. 25 The current study examined a younger cohort than the standard TJA patient; thus, pain management was viewed as a primary challenge to outpatient TJA. Advances in pain management protocols allow surgical teams to overcome many of the obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…Studies identify both orthopedic procedures and younger age as independent risk factors for higher reported pain. 25 The current study examined a younger cohort than the standard TJA patient; thus, pain management was viewed as a primary challenge to outpatient TJA. Advances in pain management protocols allow surgical teams to overcome many of the obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…This problem seems to be unsolvable but surely manageable if the patient could be monitored more closely and fastened follow-up after discharge [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Although these findings should thus be regarded with caution, they strengthen the hypothesis that women are more susceptible to experience severe postoperative acute pain. Other, smaller studies, found higher pain ratings in women admitted to the PACU [84 && ] in the first 24 h [85] and 5 postoperative days [86 && ] as well as a higher risk to develop a severe pain event in the first postoperative day (OR ÂŒ 1.14) but again with small differences [86 && ] or even no differences at all [87]. Recent pediatric studies on gender differences in postoperative pain can be consulted in Table 3.…”
Section: Miscellaneousmentioning
confidence: 99%